The hydride vapor phase epitaxy of GaN on silicon covered by nanostructures. (28th April 2016) - Jahn, U; Musolino, M; Lähnemann, J; Dogan, P; Garrido, S Fernández; Wang, J F; Xu, K; Cai, D; Bian, L F; Gong, X J; Yang, H
Abstract: GaN several tens of μ m thick has been deposited on a silicon substrate using a two-step hydride vapor phase epitaxy (HVPE) process. The substrates were covered by AlN layers and GaN nanostructures grown by plasma-assisted molecular-beam epitaxy. During the first low-temperature (low- T ) HVPE step, stacking faults (SF) form, which show distinct luminescence lines and stripe-like features in the cathodoluminescence images of the cross-section of the layers. These cathodoluminescence features provide an insight into the growth process. During a second high-temperature (high- T ) step, the SFs disappear, and the luminescence of this part of the GaN layer is dominated by the donor-bound exciton. For templates consisting of both a thin AlN buffer and GaN nanostructures, the incorporation of silicon into the GaN grown by HVPE is not observed. Moreover, the growth mode of the (high- T ) HVPE step depends on the specific structure of the AlN/GaN template, where in the first case, epitaxy is dominated by the formation of slowly growing facets, while in the second case, epitaxy proceeds directly along the c -axis. For templates without GaN nanostructures, cathodoluminescence spectra excited close to the Si/GaN interface show a broadening toward higher energies, indicating the incorporation of silicon at a high dopant level.